Evidence that rnmB is the operator of the Escherichia coli recA gene. - Volkert, M R (1981)
rnmB281 leads to high constitutive levels of recA protein such that no increase after UV-inducing treatment occurs. The mutation maps in or near the portion of recA corresponding to the NH2-terminal end of the protein. Examination of the recA proteins from rnmB+ recA-/rnmB281 recA+ heterozygotes suggests that both rnmB alleles are cis-acting and codominant. This is the behavior expected from alleles of a regulatory gene such as an operator or promoter of recA. The possibility that rnmB mutations occur in the promoter of recA. The possibility that rnmB mutations occur in the promoter of recA, though not ruled out, seems unlikely based on the structure of the regulatory region of recA. This suggests that rnmB mutations are operator constitutive mutations of the recA gene and should be called recAo mutations. The UV-irradiation responses of recAo+ and recAo281 strains, both recA+, are compared and inferences are drawn about the roles of large amounts of recA protein in producing the responses.